Exploring the effects of ambient conditions on the cryogenic cooling times of offshore structures: towards optimising sustainability and the decommissioning timescale - Kenneth Bisgaard Christensen; Alireza Maheri; M Amir Siddiq (Sustainability Science and Technology)
This study investigates the influence of ambient conditions on cryogenic cooling times for medium-carbon steel-grade ISO EN 1.0456 (ASTM A333 Gr.6) processing pipes, focusing on the air velocity, ambient temperature, and cooling medium. Using MATLAB, baseline cooling times were computed for air velocities of 0–25 m s ^−1 , considering both in-air cooling and saltwater environments. At a target temperature of −50 °C, which is critical for achieving specific impact energy absorption ( E _i ), the cooling times increased due to varying heat transfer coefficients influenced by the air velocity. Pipe wall thicknesses of 12.7 and 25.4 mm resulted in 5.7% and 6.9% increases in the cooling time, respectively. The viability of cryogenic conditions was validated for low-energy fracturing in carbon steel, utilising the MATLAB finite difference method model to simulate transient heat transfer. The impact of temperature on E _i was evaluated, and the efficiency of the proposed cryogenic cooling and cutting system was explored, incorporating factors such as air velocity and temperature. The importance of insulating effects in real-world applications was highlighted based on results obtained for the insulating residues. Validation against commercial finite element method software confirmed the accuracy of the numerical model, suggesting the broad applicability of these findings across carbon steel families. The critical role of the surface area in determining the cooling efficiency is also identified, and the trade-off between enhanced cooling, the internal surface area, costs, and energy consumption are discussed to advocate for a balanced approach. This research contributes to Sustainable Development Goals 9 (Industry, Innovation, and Infrastructure), 13 (Climate Action), and 14 (Life Bellow Water) by proposing an innovative and environmentally friendly cryogenic cooling technology to optimise the decommissioning of offshore structures. Overall, this study lays the groundwork for understanding the intricacies of cryogenic cooling to foster more sustainable and efficient manufacturing processes.